Evaluation of the Types of Processing on the Organoleptic Acceptability of the Infertile Eggs - Khaerunnisa Khaerunnisa; Nahariah Nahariah; E. Murpiningrum (Jurnal Ilmu dan Teknologi Peternakan, 2016)
Infertile eggs are the eggs that can not hatch. These eggs are only used for household consumption and  are usually processed by boiling it. There are not many studies have been done of using other methods, such as omelette and fried. The purpose of this research was to study organoleptic acceptability by panelists towards processed methods of the infertile eggs, i.e. boiled eggs, scrambled eggs and fried eggs. The results of study indicated that the average hedonic value for color of the boiled egg was 3.93 (like) and was significantly different from that of the omelette egg which was 4.6 (really like), but was similar to that of the fried egg, which was 3.83 (like). The average hedonic value for texture of boiled egg was 4.47 (really like) and was significantly different from that of the omelette, which was 3.6 (like) and fried eggs of 3.47 (like). The average value for flavor was 3.6 (like), 3.67 (like), and 3.87 (like), respectively for boiled, omelet, and fried eggs. The average value for taste for each treatment was 3.93 (like), 3.8 (like), 4.07 (like), respectively. In conclusion, treatment did not contribute to the hedonics of the panelists for flavor and taste. Processing of the infertile eggs in form of boiled, scrambled,  and fried were similar for taste and flavor, but with regards to the  color and texture, panelists  prefer  the omelette for the former and the fried eggs for latter.